2023
DOI: 10.1039/d2na00556e
|View full text |Cite
|
Sign up to set email alerts
|

Painless and sensitive pepsinogen I detection: an electrochemical immunosensor based on rhombic dodecahedral Cu3Pt and MoS2 NFs

Abstract: Gastric cancer (GC) is a common malignant tumour of the digestive tract with a high mortality rate worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Since pepsinogen is secreted by the stomach, it is not affected by short-term diet or other external conditions and enters the bloodstream through the gastric mucosa. [4][5][6][7] Therefore, the level of PG I in the serum of each individual is relatively stable and accurately reects the morphological and functional status of the gastric mucosa. Numerous studies have shown that changes in serum pepsinogen concentration are associated with diseases such as Helicobacter pylori infection, peptic ulcer disease, gastritis, and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Since pepsinogen is secreted by the stomach, it is not affected by short-term diet or other external conditions and enters the bloodstream through the gastric mucosa. [4][5][6][7] Therefore, the level of PG I in the serum of each individual is relatively stable and accurately reects the morphological and functional status of the gastric mucosa. Numerous studies have shown that changes in serum pepsinogen concentration are associated with diseases such as Helicobacter pylori infection, peptic ulcer disease, gastritis, and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%